REHABILITASI MEDIK PADA POLIOMIELITIS - Pontoh, Lely M.; Angliadi, Engeline (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Poliomyelitis (polio, infantile paralysis) is caused by a type of virus that has three serotypes: PV1, PV2, and PV3. Spreading of polio viruses from person-to-person is by faecal-oral route. Typical manifestations of poliomyelitis occur when the viruses spread, infect, and replicate in the cells of the central nervous system. The characteristic and most severe form of clinical manifestation of polio infection is paralytic polio that usually presents as asymmetrical permanent paralysis of the leg. The diagnosis of polimyelitis is confirmed based on anamnesis, physical examination, and additional examination. Medical rehabilitation programs are applied during acute, sub acute, recovery, and chronic phases.Keywords: poliomyelitis, virus, paralysis, diagnosis, medical rehabilitationAbstrak: Poliomielitis (polio, paralisis infantil) disebabkan oleh sejenis virus yang terdiri dari 3 serotipe, yaitu: PV1, PV2, dan PV3. Cara penularan penyakit ini dari manusia ke manusia melalui jalur fekal-oral. Manifestasi poliomielitis disebabkan karena penyebaran virus yang menginfeksi dan bereplikasi di dalam sel-sel sistem saraf pusat. Karakteristik dan bentuk manifestasi klinik yang paling berat dari infeksi polio ialah polio paralitik yang biasanya menyebabkan paralisis permanen asimetris pada tungkai. Diagnosis poliomielitis ditegakkan melalui anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang. Program rehabilitasi medik diterapkan pada fase akut, fase sub akut, fase penyembuhan, dan fase kronis poliomielitis.Kata kunci: poliomielitis, virus, paralisis, diagnosis, rehabilitasi medik